2013
DOI: 10.1101/gad.227454.113
|View full text |Cite
|
Sign up to set email alerts
|

Dual mechanisms prevent premature chromosome segregation during meiosis

Abstract: In meiosis I, homologous chromosomes pair and then attach to the spindle so that the homologs can be pulled apart at anaphase I. The segregation of homologs before pairing would be catastrophic. We describe two mechanisms that prevent this. First, in early meiosis, Ipl1, the budding yeast homolog of the mammalian Aurora B kinase, triggers shedding of a kinetochore protein, preventing microtubule attachment. Second, Ipl1 localizes to the spindle pole bodies (SPBs), where it blocks spindle assembly. These proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 47 publications
2
59
0
Order By: Relevance
“…This raises the intriguing question of how cells prevent S-CDK from promoting spindle formation during prolonged prophase I arrest in meiotic cells. Indeed, it has been reported that in ndt80 Δ-arrested cells, Ipl1 depletion leads to spindle formation, including multipolar spindles [23], [24]. Here, we show that in cells in which Ipl1 is inhibited or depleted, S-CDK is both sufficient and necessary to promote spindle formation during meiotic prophase I, whereas Cdc5 Polo kinase assists in the efficiency of spindle formation.…”
Section: Introductionsupporting
confidence: 45%
“…This raises the intriguing question of how cells prevent S-CDK from promoting spindle formation during prolonged prophase I arrest in meiotic cells. Indeed, it has been reported that in ndt80 Δ-arrested cells, Ipl1 depletion leads to spindle formation, including multipolar spindles [23], [24]. Here, we show that in cells in which Ipl1 is inhibited or depleted, S-CDK is both sufficient and necessary to promote spindle formation during meiotic prophase I, whereas Cdc5 Polo kinase assists in the efficiency of spindle formation.…”
Section: Introductionsupporting
confidence: 45%
“…Inhibition of meiosis I spindle formation by Aurora kinase has been reported in S. cerevisiae (Kim et al . ; Newnham et al . ), suggesting that the Aurora kinase‐dependent inhibition of meiosis progression is likely a general phenomenon, and that autophagy dysfunctions may affect this regulation.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, the spindle assembly checkpoint (SAC), a cell cycle surveillance pathway, delays chromosome segregation to allow correction of erroneous kinetochore attachments to the spindle or to allow unattached kinetochores to attach. SAC ensures proper chromosome alignment and the onset of anaphase, thereby facilitating faithful chromosome segregation (Homer et al, 2009;Musacchio and Ciliberto, 2012;Kim et al, 2013). SAC components are highly conserved across eukaryotes, including the Ser/Thr kinases monopolar spindle 1 (MPS1), Aurora and Budding Uninhibited by Benomyl 1 (BUB1), and BUB3, and the non-kinase components Mitotic Arrest Deficient 1 (MAD1), MAD2, and BUB1 Related 1 (BUBR1) (Foley and Kapoor, 2013).…”
Section: Introductionmentioning
confidence: 99%